The pricing of risk in European credit and corporate bond markets - Antje Berndt; Iulian Obreja (European Central Bank (ECB), 2007)
This paper investigates the determinants of the default risk premia embedded in the European credit default swap spreads. Using a modified version of the intertemporal capital asset pricing model, we show that default risk premia represent compensation for bearing exposure to systematic risk and to a new common factor capturing the proneness of the asset returns to extreme events. This new factor arises naturally because the returns on defaultable securities are more likely to have fat tails. The pricing implications of this new factor are not limited to credit markets only. We find that this common factor is priced consistently across a broad spectrum of corporate bond portfolios. In addition, our asset pricing tests also document patterns that are consistent with the so called "flight to quality" effect.
Keywords: G12; G13; G15; 330; credit default swap; default risk premium; European corporate bond markets; European credit market; risk factors; Kreditmarkt; Unternehmensanleihe; Kreditderivat; Risikoprämie; Eurozone; EU-Staaten